Clinical InvestigationsEffectiveness of two different HDR brachytherapy regimens with the same BED value in cervical cancer - Passi, Kamlesh; Kehwar, Than S; Mittal, Meenakshi; Singh, Bikramjit; Vashistha, Rajesh; Gupta, Sureshchandra J; Yakhmi, JV (Journal of Contemporary Brachytherapy, 2010)
Purpose: To analyze the effectiveness of biologically effective dose (BED) in two different regimens of HDR bra-chytherapy keeping the same total BED to point A and to compare the relationship of overall treatment time in terms of local control and bladder and rectal complications. Material and methods: The study included two groups comprising a total of 90 cervical cancer patients who underwent external beam radiotherapy (EBRT) followed by HDR intracavitary brachytherapy (ICBT). EBRT treatment was delivered by a Co-60 teletherapy unit to a prescribed dose of 45 Gy with 1.8 Gy per fraction in 25 fractions over a period of five weeks. Parallel opposed anterior–posterior (AP/PA) fields with no central shielding were used, followed by the HDR ICBT dose, to point A, of either two fractions of 9.5 Gy with a gap of 10 days, or three fractions of 7.5 Gy with a gap of 7 days between the fractions. Gemcitabine (dose of 150 mg/m 2 ) was given weekly to all the patients as a radiosensitizer. The calculate BED3 to point A was almost the same in both groups to keep the same late complication rates. The doses, and BED10 and BED3, were calculated at different bladder and rectal point as well as at the lymphatic trapezoid points. During and after treatment patients were evaluated for local control and complications for 24 months. Results and Conclusions: Doses and BEDs at different bladder, rectal and lymphatic trapezoid points, local control, and complications in both HDR ICBT groups did not have statistically significant differences (p > 0.05). Both HDR ICBT schedules are well tolerable and equally effective.